(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Renewable energy has gotten a lot of attention because of environmental issues like climate change, as well as political and economic reasons including decreased reliance on foreign energy imports and high oil costs. The fastest-growing renewable energy industries are wind and solar power. As advances in renewable energy are developed, the cost of power generated by renewable energy decreases. Renewable energy technologies are excellent for dispersed power generation as well as solving climate change and reducing reliance on foreign energy imports. Renewable energy may deliver power without expensive and intricate grid infrastructure in distant, there are really no power sources in remote areas, or the expense of installing distribution networks is prohibitive. Power capacity built worldwide reached 227 gigawatts (GW) in 2015, enough to need 1% of total electricity generation. Thermal power plants may be located in northern Argentina, with the largest being the 392 MW Ivanpah Solar Electric Generation System in Arizona. This paper describes and analyses a micro-grid system that includes different and independent PV sources connected to a shared DC bus, as well as localized battery storage and power monitoring and protection devices.